A pneumonia that will not go away - Khasawneh, Khaled R (Pulsus Group Inc, 2014)
Given the number of similar-appearing conditions among a widely heterogeneous group of pulmonary diseases, pneumonia is a commonly overdiagnosed entity, which makes establishing a diagnosis for a specific disease particularly challenging. This article describes the presentation, history, work-up and eventual diagnosis of a 28-year-old woman who was diagnosed with a variety conditions over a span of five months. Pneumonia is a common diagnosis with significant morbidity and mortality. However, pneumonia is a commonly overdiagnosed entity, with many similar-appearing conditions. A young, previously healthy woman was misdiagnosed with a variety of respiratory tract infections over the course of five months before establishing the correct diagnosis – chronic eosinophilic pneumonia.